2003
DOI: 10.1038/sj.ijo.0802404
|View full text |Cite
|
Sign up to set email alerts
|

Change in body mass index from adolescence to young adulthood and increased carotid intima-media thickness at 28 years of age: The Atherosclerosis Risk in Young Adults study

Abstract: Obesity has become a major health problem in Western societies by increasing the risk of atherosclerosis and cardiovascular disease. Although data on tracking of body mass index (BMI) are available, little is known about the impact of weight change over time on the development of vascular damage. OBJECTIVE: To evaluate the relationship between adolescent BMI as well as change in BMI from adolescence into young adulthood and cardiovascular risk, as estimated by common carotid intima-media thickness (CIMT). DESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 56 publications
8
74
1
8
Order By: Relevance
“…Since the 'type of school' was not significantly associated (P40.05) to the nutritional status of this sample of adolescents (Table 3) after controlling for the effects of the other variables, it is not likely that this could be a source of bias in the results that have been presented. Adolescent BMI predicts cardiovascular risk in later life (Raman, 2002;Jeffreys et al, 2003;Oren et al, 2003). Even more, overweight in adolescence has been suggested as a more powerful predictor of morbidity risks than overweight in adulthood (Must et al, 1992;Dietz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 'type of school' was not significantly associated (P40.05) to the nutritional status of this sample of adolescents (Table 3) after controlling for the effects of the other variables, it is not likely that this could be a source of bias in the results that have been presented. Adolescent BMI predicts cardiovascular risk in later life (Raman, 2002;Jeffreys et al, 2003;Oren et al, 2003). Even more, overweight in adolescence has been suggested as a more powerful predictor of morbidity risks than overweight in adulthood (Must et al, 1992;Dietz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There were therefore very few hypertensive cases to consider (16/130 men). Six studies considered the association between childhood BMI and carotid intima media thickness (CIMT) (30,(35)(36)(37)(38)(39) , with five of these studies showing a positive association (35)(36)(37)(38)(39) . However, after adjusting for adult BMI only one positive association remained, and this was for the cumulative change in BMI from childhood to adulthood (39) .…”
Section: Independent Effects Of Childhood Obesity On Adult Disease Riskmentioning
confidence: 99%
“…8,25,28,30,31 However, after adjusting for adult BMI only the cumulative change in BMI from one study 31 remained significant. An additional two studies showed positive associations with some age groups but not others.…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 99%
“…9,25,28 Adult outcomes were more homogenous, with blood pressure measured as both systolic and diastolic, and hypertension defined as per the World Health Organisation Guidelines 29 in all studies. Three studies measured CIMT in the common carotid far wall, 25,28,30 whereas two studies 8,31 averaged measurements from the far walls of the common carotid, carotid bifurcation and internal carotid. The sixth study 7 did not provide details.…”
Section: Quality Assessmentmentioning
confidence: 99%